As interfaces da LGBTfobia na gestão do trabalho em saúde - Rios, Maiquel Francisco dos Santos (2024)
The study of the relationship between gender, sexuality, and work, specifically analyzing how LGBTphobia affects the work of managers, is justified by the need to produce research on the implications it has on the work process of health managers. Objective: To investigate how managers perceive LGBTphobia in hospital health services. Method: Qualitative study with data collection strategy using a semi-structured interview script. It was carried out at a University Hospital in Rio Grande do Sul, between December 2023 and January 2024, with a sample consisting of 11 managers in leadership positions in hospital units. Result: Perspectives and behaviors of the interviewees regarding LGBTphobia in health services could be discerned. Their statements revealed various perceptions and strategies guiding their actions regarding the study's theme. Conclusion: It was possible to identify LGBTphobia manifested in a covert manner and also to perceive, through the managers' discourses, a lack of understanding and misinformation regarding the topic. In this sense, the research also encouraged managers to become more informed about the subject so that they can work with the LGBTI+ population using strategies to effectively combat situations of LGBTphobia in health services.